Cost‐effectiveness of preventing dental caries and full mouth dental reconstructions among Alaska Native children in the Yukon–Kuskokwim delta region of Alaska. (15th March 2016) - Atkins, Charisma Y.; Thomas, Timothy K.; Lenaker, Dane; Day, Gretchen M.; Hennessy, Thomas W.; Meltzer, Martin I.
Abstract: Objective: We conducted a cost‐effectiveness analysis of five specific dental interventions to help guide resource allocation. Methods: We developed a spreadsheet‐based tool, from the healthcare payer perspective, to evaluate the cost effectiveness of specific dental interventions that are currently used among Alaska Native children (6‐60 months). Interventions included: water fluoridation, dental sealants, fluoride varnish, tooth brushing with fluoride toothpaste, and conducting initial dental exams on children <18 months of age. We calculated the cost‐effectiveness ratio of implementing the proposed interventions to reduce the number of carious teeth and full mouth dental reconstructions (FMDRs) over 10 years. Results: A total of 322 children received caries treatments completed by a dental provider in the dental chair, while 161 children received FMDRs completed by a dental surgeon in an operating room. The average cost of treating dental caries in the dental chair was $1, 467 (∼258, 000 per year); while the cost of treating FMDRs was $9, 349 (∼1.5 million per year). All interventions were shown to prevent caries and FMDRs; however tooth brushing prevented the greatest number of caries at minimum and maximum effectiveness with 1, 433 and 1, 910, respectively. Tooth brushing also prevented the greatest number of FMDRs (159 and 211) at minimum and maximum effectiveness. Conclusions: All of the dental interventions evaluated were shown to produce cost savings. However, the level of that cost saving is dependent on the intervention chosen.